A Method to Measure Detonation Front Curvature of Emulsion Explosives - Nikolaos Petropoulos; Daniel Johansson; Håkan Schunnesson (International Society of Explosives Engineers)
The optimization of the explosive performance is of great importance since blasting is extensively used in civil projects and mining industry. An improved understanding of how the energy from the detonation of an explosive is transmitted to the surrounding rock mass is critical information for the proper selection of an explosive. Therefore, an extensive study was done on the influence of the blasthole diameter on the Velocity of Detonation (VoD) and the detonation front curvature. In this study, pure emulsion was tested in confined conditions to better simulate the behavior of the detonation of the explosive in rock mass conditions. A methodology is proposed for carrying out the evaluation of the explosive performance. The blasthole diameter of the samples varied from Ø 25 mm (0.98 in) up to Ø 65 mm (2.55 in). The confiner was a magnetic mortar cylindrical sample with mechanical properties similar to a rock mass. A streak camera and VoD probes were used to measure detonation front curvature and VoD. The data was analyzed and correlated with the physical parameters of the explosive. Additional to this, the data was further used to calibrate numerical models in LS-Dyna.